Association between the triglyceride glucose index and low skeletal muscle mass: a cross-sectional study - Zhenzhen Li; Jirong Yue; Ting Bao; Xiang Tong; Yao Ma (BMJ Open)
Objectives Triglyceride glucose (TyG) represents a consistent surrogate biomarker and index of insulin resistance (IR), IR has also been linked to skeletal muscle mass loss (SMM-L). Here, we evaluated the association between SMM-L and the TyG index (TyGi).Design An analytical cross-sectional study.Setting Tertiary care hospitals.Participants 36 275 participants who underwent health checks between 1 January 2013 and 31 December 2020.Primary and secondary outcome measures A bioelectrical impedance analysis was used to assess the body composition, SMM-L was defined as low ASMI (total limb lean mass/height2) and TyGi was calculated as ln(triglycerides (mg/dL)×fasting blood glucose (mg/dL)/2).Results A total of 36 275 subjects were included in the study, of which 58.46% were male, with a mean age of 43.74±12.33 years. The prevalence of low skeletal muscle mass (SMM) was 17.7% and the mean TyGi was 8.56±0.64. TyGi was found to be significantly correlated with low SMM in all subjects (OR 1.87, 95% CI 1.75 to 2.00, p<0.001), with higher correlations seen in younger subjects (OR 1.97, 95% CI 1.77 to 2.20, p<0.001), and remaining significant in middle age (OR 1.95, 95% CI 1.77 to 2.14, p<0.001), old age (OR 1.73, 95% CI 1.38 to 1.16, p<0.001), men (OR 1.60, 95% CI 1.46 to 1.76, p<0.001) and women (OR 2.59, 95% CI 2.39 to 2.87, p<0.001).Conclusions These data demonstrated a significant independent interaction between TyGi and low SMM in all subjects regardless of sex and age subgroups in the general population.